Genus key of Encyrtidae (Hymenoptera: Chalcidoidea) from Mexico and a catalog of the species: Parasitic wasps series of pests and other insects - Trjapitzin, Vladimir A. (Libros UAT, 2018)
Encyrtidae is one of the largest and most economically important families in the Chalcidoidea superfamily. By the end of 2004, 463 genera had been described in the world fauna, as well as two fossil genera. The keys for the identification of genera worldwide do not exist, only the key for the identification of encírtidos with a reduced number of artejos (less than 6) in the antennal funicle (Trjapitzin and Ruíz-Cancino, 2002 d). For the Nearctic fauna, mainly for the United States and Canada, some genre cues have been published (Trjapitzin and Gordh, 1978 a, b, Noyes et al., 1997), which include 171 genera. For the Neotropical fauna, there is the key of Noyes (1980). In Argentina a monograph of the encírtidos was published (De Santis, 1964). An important monograph on Costa Rica's encírtidos was published by Noyes (2000). For the American Continent there are some catalogs of the species of Encyrtidae: Peck (1963) and Gordh (1979) for the encírtidos to the north of Mexico; Trjapitzin and Ruíz-Cancino (1996) and Trjapitzin et al. (2004 b) for Mexico; and Trjapitzin et al. (2004 a) for Central America, West Indies and Bermuda. You can also consult the catalogs for America in southern Mexico (De Santis, 1979, 1981, 1989, De Santis and Hidalgo, 1996). In relation to the classification of the Encyrtidae Family, one can consult Trjapitzin (1973 a, b, 1989) and Trjapitzin and Gordh (1978 b). To know the use of encírtidos in biological control in Mexico, see Trjapitzin (1998 a) and the book of encírtidos of agricultural importance (Trjapitzin and Ruíz-Cancino, 2000b). This book included a chapter on the importance of the systematics of entomophagous insects for the biological control of agricultural pests, the review of the morphology of the encírtidos and a glossary of terminology in Spanish, English and Latin. The authors are grateful for their collaboration with Eunice Ruíz García for her support in capturing a part of the book. To CONACYT, for its partial support through the parasitic wasps project (Hymenoptera: Chalcidoidea) of white mosquitoes and scales in fruit trees and ornamentals of Tamaulipas, Mexico.